CRACKING THE CODE: HOW ENGLISH TEACHERS FOSTER READING COMPREHENSION AT BABUN NAJAH BOARDING - Nisa, Rahmatun; Helmanda, Cut Mawar; Husna, Mawizatul (Prologue: Journal on Language and Literature, 2025)
This study explores how English teachers at Babun Najah Boarding School develop students' reading comprehension skills through various instructional strategies. The research seeks to understand the methods they use and how these approaches impact student learning. Using a descriptive qualitative approach, data were gathered through classroom observations and interviews with both teachers and students. The findings reveal that educators employ diverse strategies, such as direct instruction, group discussions, interactive games, multimedia resources, and tailored teaching methods to meet students’ individual needs. These techniques help keep students engaged and support different learning styles. However, challenges such as students’ lack of confidence and comprehension difficulties were also identified. Teachers responded by adjusting their teaching methods to better support students. The study suggests clearly outlining learning objectives, encouraging student reflection, and integrating more collaborative and technology-driven activities. Overall, the research highlights the importance of dynamic, student-centered instruction in improving reading comprehension and offers valuable insights for enhancing English language teaching in similar educational settings.